Airport management: a perspective article. Issue 1 (13th September 2019) - Graham, Anne
Abstract : Purpose: The purpose of this paper is to present an overall viewpoint on the past (1946-2020) and future (2020-2095) development of airport management. Design/methodology/approach: The paper is based on a review of secondary literature. Findings: The paper finds that the airport industry has transformed from a public utility to a modern enterprise, with private sector ownership, more competition, the expansion of commercial facilities and more diverse business models. Originality/value: The paper provides a unique long-term and comprehensive view of past, current and future airport management, bringing together a number of linked developments, which is not found elsewhere.